ANALISIS KESULITAN MENULIS HURUF TEGAK BERSAMBUNG PADA SISWA KELAS II SDN 1 KARANGLAYUNG - Syafira, Anggi; Riga Zahara Nurani; Hatma Heris Mahendra (Universitas Pendidikan Muhammadiyah Sorong, 2026)
The ability to write connected block letters is one of the important skills that elementary school students must master, especially in the lower grades. This skill not only supports literacy skills but is also closely related to the development of children's fine motor skills. However, in practice, many students still experience difficulties in writing connected block letters consistently, neatly, and legibly. This study aims to analyze the forms and causes of difficulties in writing connected block letters among second-grade students at SDN 1 Karanglayung, Bantarkalong District. The study employs a qualitative descriptive approach with data collection techniques including observation, interviews, and writing tests. The research subjects consist of four students experiencing writing difficulties and one classroom teacher. The results of the study indicate that the students' difficulties include inconsistency in letter shapes, difficulty in smoothly connecting letters, as well as messy writing and low legibility. The factors causing these difficulties are divided into two categories: internal and external factors. Internal factors include poor fine motor coordination, low motivation to write, and limited visual perception of letter shapes. Meanwhile, external factors include a lack of structured practice, a lack of visual aids such as lined books, non-ergonomic writing posture, and a lack of support from the family environment. In conclusion, students' difficulties in writing connected block letters include inconsistent letter formation, stiff letter connections, and messy and difficult-to-read writing, which are influenced by a combination of internal and external factors. Therefore, adaptive learning strategies and adequate environmental support are needed. KEYWORDS: writing difficulties; connected block letters; fine motor skills